Quality of Life—Changes after Rhinoplasty - Niehaus, Richard; Kovacs, Lazlo; Machens, Hans-Günther; Herschbach, Peter; Papadopulos, Nikolaos A. (Facial Plastic Surgery, 2017)
Our study group has researched for >10 years in the field of Quality of Life after plastic, aesthetic, and reconstructive surgery, asking the following questions: “Does aesthetic surgery improve the Quality of Life?” and “Can a higher Quality of Life offset the risk of surgical procedures.” As part of our series of studies examining the correlation of cosmetic surgery and the postoperative well-being, this study examines the influence of rhinoplasty, as a single indication, specifically on the Quality of Life (QoL) of patients. The data of 90 patients who underwent rhinoplasty between 1997 and 2007 were prospectively collected and were retrospectively analyzed. For a competitive analysis, our evaluation was divided into the following five parts: a self-developed indication-specific questionnaire and the standardized instruments Glasgow Benefit Inventory (GBI), Questions on Life SatisfactionModules (FLZM), Freiburg Personality Inventory (FPI-R), and Rosenberg Self-Esteem Questionnaire (RSES). Numerous improvements in patients' QoL were observed. The result of the GBI (17.19) based on a scale –100 to 100 indicates an improved QoL after rhinoplasty. Significant improvements in the item relationship/sexuality were shown in the general part of the FLZM (p = 0.042). The average score (6.32) on a scale of 0 to 14 in the FPI-R questionnaire resulted in a common emotionality and self-assessment, while the RSES (33.64) on a scale 10 to 40 indicated a high self-confidence and a statistically significant improvement (p = 0.0001) compared with German norm data. The knowledge of positive social and psychological benefits and an improved sexuality in the partnership support the meaningfulness of rhinoplasty.
Keywords: quality of life; rhinoplasty; aesthetic surgery; patients' satisfaction